ОСНОВНІ ПРОБЛЕМИ РОЗВИТКУ ТА ВІДТВОРЕННЯ ТРУДОВОГО ПОТЕНЦІАЛУ УКРАЇНИ (International Journal of Innovative Technologies in Economy, 2018)
The author presents problems and perspectives for the development of the potential of labor potential in the transition from Ukraine to the innovation system. The main tendencies of the hourly rink of Ukraine are analyzed. The first tendency is to not reject the level of GDP growth, which is due to an increase in the number of dairy products. This will lead to the fact that a significant number of countries can not solve the problems encountered in the occupation, such as the high level of unemployment, disagreement, lack of access to skills, hronical gender, and unequal education. The second tendency is to mobilize the use of new people in the labor market (including in the context of maintaining employment, ensuring effective interruption from unemployment to work), which is aimed at reducing the number of people who are in the «retained» state of the bourgeoisie. The coordination of these tendencies should be able to balance and calm down, and, most of all, as well as the parameters of the inquiry and the implementation of the work in the labor market. The author defined the basic conditions for the overcoming of educational and qualification imbalances.